Exposure Condition Survey and Measurement of Defects in Compressed Stabilized Earth Block Structures in Uganda - Kerali, Anthony G.; Ekyalimpa, Ronald (Journal of Environment and Earth Science, 2017)
Inadequate provision of shelter remains a global challenge. The high cost of building materials is responsible for this situation. The compressed and stabilised earth block (CSEB) has been promoted as a low cost material. While its other properties are well understood, the behaviour of the material over time has not been properly researched. The principal objective of this research was to investigate their in-service exposure and measure defects in a humid tropical environment. Such areas are characterised by extremes of weather. The soils are also varied. The paper examines the effects of natural exposure conditions on the deterioration of CSEBs. The methodology involved literature review, visual inspection, exposure condition survey, and measurement of defects. It was confirmed that premature deterioration was widespread in exposed structures, with visible defects. The paper recommends an urgent need for improvement in the production and use of CSEBs through dissemination of location specific appropriate specifications, standards and codes. It further proposes the need for improved protective measures in the humid tropics. Additional improvement can be achieved via better intergranular bonding, reduction in voids, lowered water absorption, and protective designs and specifications. Hence, future challenges can be prevented and the effects of identified deterioration agents minimised
Keywords: Building Survey, Compressed Stabilised Earth Blocks, Defects, Exposure Condition, Structures